The Democracy Monument: Ideology, Identity, and Power Manifested in Built Forms - Noobanjong, Koompong (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This research article examines the methods of power mediation in the design of the Democracy Monument in Bangkok, Thailand. It examines its underlying concept and mechanisms for conveying political power and social practice, along with the national and cultural identity that operates under an ideological framework. The study consists of two major parts. First, it investigates the monument as a political form of architecture: a symbolic device for the state to manifest, legitimize, and maintain power. The focus then shifts to an architectural form of politics: the ways in which ordinary citizens re-appropriated the Democracy Monument through semantic subversions to perform their social and political activities as well as to form their modern identities. Via the discourse theory, the analytical and critical discussions further reveal complexity, incongruity, and contradiction of meanings in the design of the monument in addition to paradoxical relationships with its setting, Rajadamnoen Avenue, which resulted from changes in the country’s socio-political situations.